Pentingnya Literasi Informasi dalam Menghadapi Tantangan Informasi Palsu (Hoaks) - Sabily Rusdiyanti; Begung Hutagalung; Ruly Afandi; Sheva Maulana Firmansyah; Denny Oktavina Radianto (Universitas Dehasen Bengkulu, 2023)
In the era of digitally connected information, the challenge of false information or hoaxes is increasingly challenging. False information can cause significant harm, including public confusion, wrong decisions, and even potential harm. Therefore, it is important to develop strong information literacy in dealing with this challenge. This study aims to highlight the importance of information literacy in dealing with hoaxes. Information literacy includes individual abilities to access, evaluate, understand, and use information critically. With good information literacy, individuals can distinguish between accurate and reliable information and false or biased information. In dealing with hoaxes, information literacy provides significant benefits. First, individuals are equipped with the ability to identify hoaxes through traits such as untrusted sources or use of emotional language. Second, they can verify information by checking facts and using reliable sources. Third, information literacy helps in developing a skeptical attitude towards information, so that individuals do not immediately receive information without critical consideration. Finally, information literacy allows for a better understanding of the context of information, including the motives behind spreading hoaxes and the interests involved. Increasing information literacy is important in overcoming the challenge of false information. Education and training that focuses on information literacy needs to be introduced in the education curriculum and also carried out outside the school environment. Through a better understanding of information literacy, individuals can develop higher digital intelligence, make smarter decisions, and contribute to a more informational and democratic society. In order to build a society that is critical of false information, collaboration between educational institutions, the government, the media industry and the wider community is needed. By combining these efforts, we can fight false information and maintain information integrity in an era full of hoaxes.